Fuzzy Logic Application in Boron and Cadmium Analysis in U3O8 use of Emission Spectrograph Method - S. Simbolon; Supriyono Supriyono; Aryadi Aryadi; T. Rahardjo (PPIKSN-BATAN, 2011)
Boron and cadmium in U3O8 have been analyzed with emission spectrograph. Three inputs of emission spectrograph, current (A), exposure time (second) and gap between electrodes (mm) were varied. Two outputs, boron and cadmium lines intensities respectively were selected and measured. Thirteen experiments have been carried out and data found were calculated by fuzzy logic Mamdani-type. Three and five memberships functions of straight-line (Triangular, Trapezoidal), Generalized-bell and Gaussian curve were used to analyze the found data. The result found that five memberships functions had less error percentage range than three memberships functions of straight-line (Triangular, Trapezoidal), Generalized-bell and Gaussian curve. The error percentage range of cadmium analysis was wider than boron analysis with this method. Analysis of cadmium in U3O8 with this method needs much exposure time compare to analysis of boron. Received: 28 December 2009; Revised: 29 November 2010; Accepted: 8 February 2011